VD_FINDINFO HC / 2022 / 620 vom 14. Juli 2022 - VD Tribunal cantonal (2022)
APPEL EN CAUSE, ACTION EN LIBÉRATION DE DETTE, CONNEXITÉ MATÉRIELLE | 319 let. b ch. 1 CPC (CH), 81 al. 1 CPC (CH), 82 al. 4 CPC (CH)